Transformational leadership and employee performance through affective commitment in public universities in Southwest Afghanistan - Nasim Tahsildar; Asmatullah Qani (Discover Education, 2026)
Abstract This study examines the relationship between transformational leadership and employee performance, with affective commitment as a mediating mechanism, among academic and administrative staff in public universities in Southwest Afghanistan. Grounded in Social Exchange Theory, the study explores how leadership behaviors influence employee attitudes and work outcomes in a resource-constrained higher education context. A convergent mixed-methods design was employed, combining survey data collected through purposive sampling with semi-structured interviews. Quantitative data were analyzed using correlation, regression, and mediation techniques, while qualitative data were examined through thematic analysis. The findings indicate that transformational leadership positively affects employee performance both directly and indirectly through affective commitment. Employees who perceive their leaders as supportive, inspirational, and fair are more likely to develop stronger emotional attachment to their institutions and achieve higher performance. Qualitative evidence further emphasizes the importance of communication, fairness, motivation, and institutional support. This study extends transformational leadership research to an underexplored higher education context and offers practical implications for strengthening leadership capacity and organizational effectiveness in public universities.